Magnetic particles

By controlling the difference in the proportion of cobalt elements in magnetic particles below 19atom%, the problem of increasing magnetic loss in the GHz frequency band is solved, and the low loss and high stability of magnetic particles are achieved.

CN120457503APending Publication Date: 2025-08-08MURATA MFG CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380089960.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-01-16
Filing Date
2023-08-24
Publication Date
2025-08-08

AI Technical Summary

Technical Problem

The prior art cannot effectively reduce magnetic loss caused by magnetic resonance in the GHz frequency band, especially when magnetic particles are used, the magnetic loss is significantly increased.

Method used

By controlling the proportion of cobalt elements in the magnetic particles to the total element of iron and nickel elements, the difference between the maximum value and the minimum value in the cross-section is less than 19atom%, thereby reducing the composition deviation, thereby suppressing the fluctuation of the relative magnetic permeability of the magnetic particles.

Benefits of technology

It effectively reduces the magnetic loss in magnetic resonance, improves the relative magnetic permeability stability of magnetic particles, and reduces the loss at high frequency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120457503A_ABST
    Figure CN120457503A_ABST
Patent Text Reader

Abstract

Provided are magnetic particles in which the difference between the maximum value and the minimum value measured along the maximum diameter of a cross-section is 19 atom% or less, in the element ratio of elemental cobalt to the total of elemental iron, elemental nickel, and elemental cobalt in the cross-section.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to magnetic particles. Background Art

[0002] In the past, as inductor components using magnetic particles, there are inductor components described in Japanese Patent Application Publication No. 2018-37635 (Patent Document 1), Japanese Patent Application Publication No. 2008-277775 (Patent Document 2), and Japanese Patent Application Publication No. 5-217730 (Patent Document 3). The inductor component of Patent Document 1 includes a magnetic composition, which includes first metal magnetic particles with an average particle size of 10 to 28 μm, second metal magnetic particles with an average particle size of 1 to 4.5 μm, and third metal magnetic particles with an insulating film provided on the surface and a particle size of 300 nm or less as metal magnetic particles. Patent Document 2 describes a method for manufacturing a powder core, characterized in that a soft magnetic powder with Fe as the main component is immersed in an alkoxide solution to form an insulating oxide film on the entire or a portion of the powder surface, and then an inorganic binder is mixed, pressed and molded, and then heat-treated at above 600°C. Patent Document 3 describes an amorphous magnetic film formed by winding or laminating amorphous magnetic thin plates having an electrically insulating plasma polymerized film coating layer provided on the surface.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Laid-Open No. 2018-37635

[0006] Patent Document 2: Japanese Patent Application Laid-Open No. 2008-277775

[0007] Patent Document 3: Japanese Patent Application Laid-Open No. 5-217730 Summary of the Invention

[0008] However, as described below, it is difficult to reduce the magnetic loss caused by magnetic resonance in the above-mentioned Patent Documents 1 to 3.

[0009] Magnetic loss includes eddy current loss and hysteresis loss. In order to reduce eddy current loss, it is considered to micronize and form an insulating layer on the particle surface (Patent Document 1). In order to reduce hysteresis loss, it is considered to remove strain by heat treatment (Patent Document 2) and use amorphous powder with low crystallinity (Patent Document 3). These methods are effective in the operating frequency of power inductors, etc., that is, in hundreds of MHz bands.

[0010] However, the inventors have recently discovered that magnetic losses increase due to magnetic resonance in the higher GHz band, a problem that cannot be addressed by Patent Documents 1 to 3. For example, when magnetic particles are used at higher frequencies than those used in RF inductors, magnetic losses due to magnetic resonance can become significant.

[0011] Therefore, an object of the present invention is to provide magnetic particles capable of reducing fluctuations in relative magnetic permeability during magnetic resonance and reducing magnetic loss.

[0012] To solve the above problems, in a magnetic particle according to one embodiment of the present disclosure, the difference between the maximum and minimum values of the element ratio of cobalt to the total of iron, nickel, and cobalt in a cross section measured along the maximum diameter of the cross section is 19 atom % or less.

[0013] By controlling the element ratio of the cobalt element and suppressing compositional variations as described above, it is possible to reduce fluctuations in the relative magnetic permeability of the magnetic particles and reduce magnetic loss.

[0014] According to the present disclosure, it is possible to provide magnetic particles capable of reducing fluctuations in relative magnetic permeability during magnetic resonance and reducing magnetic loss. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is a perspective view showing a first embodiment of the inductor component according to the present invention.

[0016] Figure 2 is an exploded view of the inductor components.

[0017] Figure 3 This is a cross-sectional view of the inductor component taken along the line X-X.

[0018] Figure 4 This is an explanatory diagram illustrating a portion of the internal magnetic member of an inductor component.

[0019] Figure 5 This is an explanatory diagram for explaining the measurement of the maximum diameter.

[0020] Figure 6A This is a graph showing the measured element ratio of cobalt atoms in Example 1.

[0021] Figure 6B This is a graph showing the measurement of the real part μ' of the magnetic permeability and the imaginary part μ" of the magnetic permeability in Example 1.

[0022] Figure 7A This is a graph showing the measured element ratio of cobalt atoms in Example 2.

[0023] Figure 7B This is a graph showing the measurement of the real part μ' of the magnetic permeability and the imaginary part μ" of the magnetic permeability in Example 2.

[0024] Figure 8A This is a graph showing the measured element ratio of cobalt atoms in Comparative Example 1.

[0025] Figure 8B This is a graph showing the measurement of the real part μ' of the magnetic permeability and the imaginary part μ" of the magnetic permeability in Comparative Example 1. DETAILED DESCRIPTION

[0026] Hereinafter, the magnetic particles as one embodiment of the present disclosure will be described in more detail by way of the illustrated embodiments. It should be noted that some of the drawings are schematic and may not reflect actual dimensions or proportions.

[0027] (First embodiment)

[0028] Figure 1 It is a perspective view showing a first embodiment of the inductor component 1 . Figure 2 is an exploded view of the inductor component 1. Figure 3 It is a XX cross-sectional view of the inductor component 1 . Figure 4 This is an explanatory diagram for explaining internal magnetic components of the inductor component 1 . Figure 5 This is an explanatory diagram for explaining the measurement of the maximum diameter D.

[0029] like Figures 1 to 3 As shown, the inductor component 1 includes a main body 10 , a coil 20 provided on the main body 10 , and a first external electrode 30 and a second external electrode 40 provided on the main body 10 and electrically connected to the coil.

[0030] Inductor component 1 is electrically connected to wiring on a circuit board (not shown) via first and second external electrodes 30 and 40. Inductor component 1 is used, for example, as an impedance matching coil in high-frequency circuits and is used in electronic devices such as personal computers, DVD players, digital cameras, TVs, mobile phones, automotive electronics, and medical and industrial equipment. However, the applications of inductor component 1 are not limited to these; for example, it can also be used in tuning circuits, filter circuits, and rectifier and smoothing circuits.

[0031] The body 10 further includes an insulator 11 , a first outer magnetic member 61 , a second outer magnetic member 62 , and an inner magnetic member 63 .

[0032] Insulator 11 comprises glass. More specifically, insulator 11 is formed from a sintered glass body. Examples of glass include borosilicate glass. Insulator 11 may further include non-magnetic ferrite, alumina, resin, and the like. Insulator 11 is formed from a plurality of insulating layers stacked in the W direction. Each layer is layered, extending along the LT plane perpendicular to the stacking direction in the W direction. It should be noted that due to the sintering process, the interface between adjacent layers may sometimes be unclear.

[0033] The main body 10 is formed into a substantially rectangular parallelepiped shape. The main body 10 includes a first end face 13 and a second end face 14 that oppose each other, a third end face 15 and a fourth end face 16 that oppose each other, a bottom face 17 that connects between the first and second end faces 13 and 14 and between the third and fourth end faces 15 and 16, and a top face 18 that opposes the bottom face 17. Specifically, the outer surface of the main body 10 is composed of the first end face 13, the second end face 14 that opposes the first end face 13, the third end face 15 that connects between the first and second end faces 13 and 14, the fourth end face 16 that opposes the third end face 15, the bottom face 17 that connects between the third and fourth end faces 15 and 16, and the top face 18 that opposes the bottom face 17. It should be noted that, as shown in the figure, the L direction is a direction perpendicular to the first end surface 13 and the second end surface 14, the W direction is a direction perpendicular to the third end surface 15 and the fourth end surface 16, and the T direction is a direction perpendicular to the bottom surface 17 and the top surface 18. The L direction, the W direction, and the T direction are orthogonal to each other.

[0034] The coil 20 has a spiral structure wound along the coil axis so that the coil axis is parallel to the bottom surface 17 of the main body 10 and intersects the third end surface 15 and the fourth end surface 16 of the main body 10 .

[0035] The coil 20 is formed into a roughly rectangular shape when viewed from the axial direction, but is not limited to this shape. The shape of the coil 20 can be, for example, circular, elliptical, rectangular, or other polygonal shapes. The axial direction of the coil 20 refers to the direction parallel to the central axis of the spiral around which the coil 20 is wound. The axial direction of the coil 20 is in the same direction as the stacking direction of the insulating layer. The term "parallel" in this application is not limited to an exact parallel relationship, but also includes a substantially parallel relationship, taking into account the range of actual deviations.

[0036] The coil 20 includes a coil wiring 21 wound along a plane. A plurality of coil wirings 21 are stacked along the axial direction. The coil wiring 21 is formed by winding on the main surface (LT plane) of the insulating layer perpendicular to the axial direction. The coil wirings 21 adjacent to each other in the stacking direction are electrically connected in series via the via wiring 26 that penetrates the insulating layer in the thickness direction (W direction). That is, the coil 20 includes the coil wiring 21 and the via wiring 26. In this way, the plurality of coil wirings 21 are electrically connected in series to form a spiral. Specifically, the coil 20 has a structure in which a plurality of coil wirings 21 are stacked, which are electrically connected in series and have a winding number of less than 1 turn. The coil wiring 21 is composed of a single layer of coil conductor layer. It should be noted that the coil wiring 21 can be composed of multiple layers of coil conductor layers stacked in surface contact with each other. In this case, a coil wiring 21 with a high aspect ratio and high rectangularity can be formed. In addition, the coil wiring 21 can be a spiral shape with more than 1 turn.

[0037] The coil 20 includes Ag. The coil 20 may include a conductive material other than Ag (for example, Cu, Au, etc.) and glass.

[0038] The first external electrode 30 is L-shaped and extends across the first end surface 13 and the bottom surface 17. The second external electrode 40 is L-shaped and extends across the second end surface 14 and the bottom surface 17. In other words, both the first external electrode 30 and the second external electrode 40 are exposed at the bottom surface 17. The first external electrode 30 is connected to the first end of the coil 20, and the second external electrode 40 is connected to the second end of the coil 20.

[0039] The first external electrode 30 is composed of two layers: a base electrode layer 31 and a plating layer 32. The second external electrode 40 is composed of two layers: a base electrode layer 41 and a plating layer 42.

[0040] The base electrode layer 31 is composed of multiple external electrode conductor layers 33 stacked in surface contact with each other. The base electrode layer 41 is composed of multiple external electrode conductor layers 43 stacked in surface contact with each other. The base electrode layers 31 and 41 can be composed of, for example, a conductive material such as Ag, Cu, or Au and glass particles, or can be formed of the same material as the coil 20. The external electrode conductor layers 33 and 43 can be embedded in the main body 10 or formed on the outer surface of the main body 10.

[0041] The plated layers 32 and 42 are formed by, for example, Ni, Sn, Au, or Cu plating, and more specifically, by Ni and Sn plating.

[0042] The first external magnetic member 61 and the second external magnetic member 62 are present on the outside of the coil 20 in the axial direction of the coil 20. The first external magnetic member 61 constitutes the third end face 15 of the main body 10, and the second external magnetic member 62 constitutes the fourth end face 16 of the main body 10. The first external magnetic member 61 and the second external magnetic member 62 contain magnetic materials and can be composed of a composite of resin and magnetic materials. It should be noted that in this specification, a magnetic member refers to a member containing magnetic material and may not contain resin. It should be noted that other members such as an insulating layer can be stacked (coated) with a resin material or an inorganic material on the outer surface side of the first external magnetic member 61 and the second external magnetic member 62 for the purpose of insulation and protection. That is, by providing other members, it is possible to suppress the peeling of the first external magnetic member 61 and the second external magnetic member 62, the generation of cracks, the short circuit between the first external electrode 30 and the second external electrode 40, and the generation of current leakage.

[0043] The inner magnetic member 63 is connected to the first outer magnetic member 61 and the second outer magnetic member 62. The inner magnetic member 63 exists inside the coil 20 in the axial direction of the coil 20.

[0044] Figure 4 Yes Figure 3 FIG. 6 is a schematic diagram showing the region A of the internal magnetic member 63. Figure 3 、 4 As shown, the internal magnetic member 63 is composed of a composite of resin 71 and magnetic particles 72 contained within the resin 71. This configuration improves DC superposition characteristics compared to magnetic layers composed of ferrite. Furthermore, this configuration reduces losses (eddy current loss and hysteresis loss) at high frequencies because the magnetic particles 72 are insulated by the resin 71. The internal magnetic member 63 can be made of the same material as the first and second external magnetic members 61, 62.

[0045] The resin 71 is, for example, epoxy resin.

[0046] The magnetic particles 72 are single particles in this embodiment. However, the magnetic particles 72 may be an aggregate of a plurality of particles (ie, an aggregate of particles that are simply aggregated without being connected) or a granular mass formed by sintering or connecting a plurality of particles.

[0047] The magnetic particles 72 are made of an alloy containing iron (Fe), nickel (Ni), and cobalt (Co). The alloy may be an amorphous alloy.

[0048] like Figure 5 As shown, the magnetic particle 72 has a maximum diameter D, an outer measurement range Z′, a measurement range Z, a straight line L1 along the maximum diameter D, and a measurement area Y.

[0049] The maximum diameter D is the largest diameter in a cross section of the magnetic particle 72. It should be noted that when the cross section of the magnetic particle 72 is elliptical, the maximum diameter D refers to the maximum length in the long axis direction. When the magnetic particle 72 is an aggregate or a mass, the maximum diameter D refers to the maximum length in the cross section. The maximum diameter D can be the maximum diameter of the magnetic particle 72 in any cross section; it does not need to be the cross section where the longest diameter of the magnetic particle 72 occurs.

[0050] The measurement range Z and the measurement-outside range Z' exist within the maximum diameter D. The sum of the measurement range Z and the measurement-outside range Z' equals the maximum diameter D. When the maximum diameter D is set to 100%, the measurement-outside range Z' represents 10% of the distance from the surface of the magnetic particle 72 along the maximum diameter D. In the measurement-outside range Z', the composition of the resin 71 present in the depth direction is detected, so the elemental composition cannot be accurately determined. Therefore, the measurement range Z represents the range of 10 to 90% of the distance from one surface of the magnetic particle 72 along the maximum diameter D.

[0051] The straight line L1 is provided along the maximum diameter D.

[0052] The measurement area Y represents a region within the measurement range Z encompassing a certain width in a direction perpendicular to line L1. Here, "certain width" refers to an aspect ratio, i.e., a ratio relative to the maximum diameter D, of -2.5% to 2.5% relative to 100% of the maximum diameter D. The elemental composition of cobalt, described later, is measured within the measurement area Y. The phrase "measurement along the maximum diameter" used herein refers to measurements within the measurement area Y.

[0053] In the magnetic particles 72, the variation in the elemental proportion of the cobalt element in the measurement area Y is less than 19 atom%, preferably less than 9 atom%. The lower limit of the variation in the elemental proportion of the cobalt element is, for example, more than 1 atom%, more preferably more than 2 atom%. The elemental proportion of the cobalt element (atom%, element percentage) can be calculated by the ratio of the cobalt element to the total of the iron element, the nickel element and the cobalt element, that is, 100×Co / (Fe+Ni+Co). By having such an elemental proportion, the composition deviation in the magnetic particles 72 can be suppressed. As a result, the variation in the relative magnetic permeability in the magnetic particles 72 can be reduced, and the magnetic loss can be reduced. It should be noted that the variation in the elemental proportion of the cobalt element only needs to be within the above-mentioned numerical range in the measurement area Y in any cross-section of the magnetic particle 72. As long as the variation in the elemental proportion of the cobalt element in the measurement area Y in any cross-section of the magnetic particle 72 is within the above-mentioned numerical range, the magnetic loss can be reduced compared to the case outside the above-mentioned numerical range.

[0054] The element ratio of cobalt element was determined as follows.

[0055] A focused ion beam (FIB) is used to form a cross section from the internal magnetic member 63. In the cross section, an arbitrarily selected magnetic particle 72 is selected. Energy dispersive X-ray spectroscopy (TEM / EDX) is used to irradiate the magnetic particle 72 with an electron beam in the direction of the maximum diameter D. In the magnetic particle 72, the difference between the maximum and minimum values of the cobalt element in the measurement area Y is calculated, and this difference is defined as the "change in the element ratio of the cobalt element." Since the detection limit of TEM / EDX is considered to be around 1 atom%, values below 1 atom% are judged to be undetectable.

[0056] The particle size of the magnetic particles 72 is, for example, 1 μm or less. During the manufacturing stage of the inductor component 1, the particle size of the magnetic particles 72 can be measured using an electron microscope. When the particle size of the magnetic particles 72 is 1 μm or less, the DC superposition characteristics are further improved, and the iron loss at high frequencies can be reduced by fine powder. The particle size of the magnetic particles 72 is, for example, 0.1 μm or more. In this case, uniform dispersion in the resin becomes easy, and the manufacturing efficiency of the internal magnetic component 63 is improved. The content of the magnetic particles 72 is preferably 20 vol% to 70 vol% relative to the entire internal magnetic component 63.

[0057] The variation of the relative magnetic permeability is, for example, less than 2.5%, specifically less than 1.5%. Here, the variation of the relative magnetic permeability refers to the difference between the maximum and minimum values of the relative magnetic permeability in the range of 200 MHz to 2 GHz. If the relative magnetic permeability varies, the loss increases on the low-frequency side compared to when the relative magnetic permeability is uniform. However, by making the variation of the relative magnetic permeability within the above range, the magnetic loss can be suppressed, especially on the low-frequency side, as in the case of uniform relative magnetic permeability. When an inductor component containing magnetic particles 72 is used as a matching component in a circuit, magnetic particles 72 with little variation in relative magnetic permeability can be easily used.

[0058] The above-mentioned change in relative magnetic permeability was measured as follows.

[0059] The frequency characteristics of relative magnetic permeability in the composite of resin 71 and magnetic particles 72 were measured in the range of 200 MHz to 2 GHz. The average value of the relative magnetic permeability and the maximum and minimum values derived from magnetic resonance were determined. The difference between the maximum and minimum values, assuming the average value of the relative magnetic permeability was 100%, was calculated. The change in relative magnetic permeability due to magnetic resonance is the difference between the maximum and minimum values. The maximum value refers to the point with the maximum amplitude in the positive direction, while the minimum value refers to the point with the maximum amplitude in the negative direction.

[0060] In this method, the average Q value is a good value. Here, the average Q value refers to the average value of the Q value obtained in the range of 200MHz to 2GHz. The Q value refers to the ratio of the real part μ' of the magnetic permeability to the imaginary part μ" of the magnetic permeability, that is, μ' / μ". The average Q value is, for example, 5.0×10 1 More than, specifically 1.0×10 3 Here, the real part μ' of the effective permeability is the permeability of the part that actually functions as an inductor, and the imaginary part μ" of the permeability represents a value related to loss. If the real part μ' of the permeability decreases, the imaginary part μ" of the permeability increases.

[0061] The present invention is not limited to the first embodiment described above, and design changes can be made within the scope of the present invention. The magnetic component can have at least one particle that satisfies the above conditions. In the magnetic component, preferably all particles satisfy the above conditions.

[0062] For example, the magnetic particles 72 may be used in other applications, as a radio wave absorber, or in electronic components such as capacitor components.

[0063] The cobalt element in the magnetic particles 72 was measured as follows.

[0064] Magnetic particles 72 were fixed to a sheet-like shape using a holder such as the resin 71 of the present invention. A cross-section of the sheet was then formed using FIB as described above. In this cross-section, an electron beam was irradiated along the direction of the maximum diameter D of the magnetic particles 72 using a TEM / EDX system. The difference between the maximum and minimum values of the cobalt element in the measurement region Y of the magnetic particles 72 was determined, and this difference was defined as the "change in the elemental ratio of the cobalt element."

[0065] For example, the magnetic particles 72 may be a sheet-shaped magnetic material containing magnetic particles. In this embodiment, it is possible to control the system so that radio waves at a specific frequency are lost and do not enter the system.

[0066] The cobalt element in the magnetic member was measured as follows.

[0067] A composite of resin 71 and magnetic particles 72 contained within the resin 71 is formed into a sheet. A cross-section is then formed on the sheet using FIB as described above. Five randomly selected magnetic particles 72 are selected from the cross-section. Using a TEM / EDX system, electron beams are irradiated along the direction of the maximum diameter D of each of the five magnetic particles 72. For each magnetic particle 72, the difference between the maximum and minimum values of the cobalt element in the measurement region Y is determined. The maximum difference is defined as the "change in the cobalt element ratio."

[0068] The materials are not limited to the above-mentioned materials, and known materials can be used.

[0069] The present disclosure includes the following aspects.

[0070] <1>

[0071] A magnetic particle having a cross-section in which the difference between a maximum value and a minimum value of an element ratio of cobalt element to a total of iron element, nickel element, and cobalt element measured along the maximum diameter of the cross-section is 19 atom % or less.

[0072] <2>

[0073] The magnetic particle according to <1>, wherein the difference between the maximum value and the minimum value is 9 atom % or less.

[0074] <3>

[0075] The magnetic particle according to <1> or <2>, wherein the particle diameter is 1 μm or less.

[0076] <4>

[0077] A magnetic member includes a resin and the magnetic particles described in any one of <1> to <3> contained in the resin.

[0078] <5>

[0079] An inductor component includes a main body including the magnetic member described in <4> and a coil provided in the main body.

[0080] Example

[0081] The present disclosure will be described in detail with reference to the following examples, but the present disclosure is not limited to these examples.

[0082] (Example 1)

[0083] (Operation 1)

[0084] Add iron sulfate heptahydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate (all manufactured by Wako Pure Chemical Industries, Ltd.) to pure water and stir and dissolve using a magnetic stirrer to prepare a metal salt solution. The total metal ion concentration is 0.3 M (Fe:Co:Ni = 2:1:1), and the volume of the metal salt solution is 50 mL.

[0085] (Operation 2)

[0086] 18 g of a hydrazine aqueous solution (produced by Wako Pure Chemical Industries, Ltd.) and 7.6 g of sodium hydroxide (produced by Wako Pure Chemical Industries, Ltd.) were added to pure water, and stirred and dissolved using a magnetic stirrer to prepare an aqueous solution of a reducing agent.

[0087] (Operation 3)

[0088] The metal salt solution was heated to 70°C in a water bath and stirred at 200 rpm using a Teflon (registered trademark) stirring blade. The reducing agent was added dropwise to the metal salt solution at a delivery rate of 3.3 mL / min using a liquid delivery pump (FP100-1, AS ONE).

[0089] (Operation 4)

[0090] After the addition of the reducing agent was completed, stirring was continued at 70° C. for 2 hours. After the reaction was completed, the solution was allowed to stand at room temperature, and the solution and the precipitate were separated by magnetic separation.

[0091] After adding 50 mL of pure water to the precipitate, magnetic separation was performed again to wash the precipitate. This operation was repeated three times in total.

[0092] Then, acetone (manufactured by Nacalai Tesque) was added to perform solvent replacement, and the obtained powder was naturally dried on a metal tray for 3 hours and recovered.

[0093] <Film Production>

[0094] The powder obtained in Example 1 was mixed with an epoxy resin and formed into a sheet using a spatula. A 5 mm x 18 mm sheet was cut out from the sheet, and the thickness of the sheet was measured using a micrometer.

[0095] <Determination of the element ratio of cobalt>

[0096] The above-mentioned sheet was cross-sectioned using FIB (SMI-3050R manufactured by Hitachi High-Tech), and the cross section was irradiated with an electron beam using TEM / EDX (JEM-F200 / Noran System 7 manufactured by JEOL) for line scanning. The elemental proportions of iron, cobalt, and nickel were measured respectively. In the measurement of the elemental proportions, for example, when the maximum diameter D of the magnetic particles is 100 nm, the 10 nm at the left and right ends are set as the measurement outer range Z', and the area of 80 nm in the range of 10 to 90 nm in the center is set as the measurement range Z. Measurement points are set on L1 at intervals of 0.5 nm, and the elemental proportions are measured in the measurement area Y. It should be noted that the width of the measurement area Y is in the range of -2.5% to 2.5% relative to the maximum diameter D. The elemental proportion of the cobalt element Co / (Fe+Ni+Co)×100 is calculated from the obtained elemental proportions. The results are shown in Figure 6A and Table 1.

[0097] <Relative Permeability Change and Q Value Measurement>

[0098] The frequency characteristics of the relative magnetic permeability of the sheet were measured using an E5071C (manufactured by Keysight Technologies, Inc.). The average relative permeability (100%) and the maximum and minimum values due to magnetic resonance were determined within the range of 200 MHz to 2 GHz. The absolute value of the difference between the maximum and minimum values was defined as the variation in relative permeability due to magnetic resonance.

[0099] Similarly, the average value Qave of the Q value (μ' / μ") at 200 MHz to 2 GHz was measured.

[0100] The results are shown in Figure 6B and Table 2.

[0101] (Example 2)

[0102] The same operation as in Example 1 was performed except that the liquid feeding rate was 10.0 ml per minute. The results are shown in FIG. Figure 7A 、 Figure 7B and Tables 1-2.

[0103] (Comparative Example 1)

[0104] The same operation as in Example 1 was performed except that the liquid feeding rate was 0.65 ml per minute. The results are shown in FIG. Figure 8A 、 Figure 8B and Tables 1-2.

[0105] [Table 1]

[0106]

[0107] [Table 2]

[0108]

[0109] As shown in Comparative Example 1, when the variation in the cobalt element ratio is high, the variation in relative permeability is large, and the average Q value (Qave) is small. In other words, it can be seen that when the variation in the cobalt element ratio is high, compositional nonuniformity occurs within the magnetic particles.

[0110] In contrast, in Example 1, the variation in the elemental ratio of cobalt was 19 atom%, and the compositional variation was controlled. In Example 1, the variation in the relative magnetic permeability of the magnetic particles was small, the magnetic loss was reduced, and the average Q value was small.

[0111] Furthermore, in Example 2, the variation in the cobalt content was 9 atom%, and the compositional variation was further controlled. Therefore, in Example 2, the variation in the relative magnetic permeability of the magnetic particles was further reduced, the magnetic loss was further reduced, and the average Q value was further reduced.

[0112] This application claims priority based on Japanese Patent Application No. 2023-004637 filed in Japan on January 16, 2023, the entire contents of which are incorporated herein by reference.

[0113] Explanation of symbols

[0114] 1 Inductor components

[0115] 10 Main Body

[0116] 13 First end face

[0117] 14 Second end face

[0118] 15 Third end face

[0119] 16 Fourth end face

[0120] 17 Bottom

[0121] 18 Top

[0122] 20 coils

[0123] 21 Coil wiring

[0124] 26 Via wiring

[0125] 30 first external electrode

[0126] 40 second external electrode

[0127] 31, 41 base electrode layer

[0128] 32, 42 coating layers

[0129] 61 first external magnetic member

[0130] 62 second external magnetic member

[0131] 63 internal magnetic components

[0132] 71 resin

[0133] 72 magnetic particles

[0134] D Maximum diameter

[0135] Z measurement range

[0136] Z' outside the measurement range

[0137] Real part of μ' magnetic permeability

[0138] μ” is the imaginary part of the magnetic permeability

[0139] L1 is along the line of maximum diameter

[0140] Y measurement area

Claims

1. A magnetic particle, wherein the difference between the maximum and minimum values of the element ratio of cobalt element to the total of iron element, nickel element, and cobalt element in a cross section measured along the maximum diameter of the cross section is 19 atom % or less.

2. The magnetic particle according to claim 1, wherein The difference between the maximum value and the minimum value is 9 atom % or less. The magnetic particle according to claim 1 or 2, wherein the particle size is 1 μm or less. 4 . A magnetic member comprising a resin and the magnetic particles according to claim 1 contained in the resin. 5 . An inductor component comprising: a main body including the magnetic member according to claim 4 ; and a coil provided in the main body.

Citation Information

Patent Citations

  • Amorphous magnetic material covered with plasma polymerized film

    JP1993217730A

  • Dust core and its manufacturing method

    JP2008277775A

  • Magnetic material composition, inductor and magnetic material main body

    JP2018037635A

  • Mold transformer

    JP2023004637A